2016
DOI: 10.1111/andr.12215
|View full text |Cite
|
Sign up to set email alerts
|

Intervention improves assisted conception intracytoplasmic sperm injection outcomes for patients with high levels of sperm DNA fragmentation: a retrospective analysis

Abstract: SUMMARYSperm DNA fragmentation (SDF) is used in assisted reproductive technology (ART) programs as an indicator for sperm quality, although there is still a lack of consensus as to its clinical utility. In this retrospective study, we examined intracytoplasmic sperm injection (ICSI) outcomes of 1924 infertile patients who underwent SDF analysis using the sperm chromatin integrity test. ART patients were classified as having low [DNA fragmentation index (DFI) <29%] or high SDF (DFI ≥29%) and by whether or not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 36 publications
4
87
0
2
Order By: Relevance
“…Ovarian stimulation, oocyte collection, and fertilization with sperm were performed as described previously (6,14). Embryo culture to the blastocyst stage was performed in groups of up to five embryos as described previously (6) with either in-house manufactured sequential media identical in formulation to Sydney IVF embryo culture medium suite (Cook Medical) or Gems sequential embryo culture media (Genea Biomedx).…”
Section: General Assisted Reproduction Proceduresmentioning
confidence: 99%
“…Ovarian stimulation, oocyte collection, and fertilization with sperm were performed as described previously (6,14). Embryo culture to the blastocyst stage was performed in groups of up to five embryos as described previously (6) with either in-house manufactured sequential media identical in formulation to Sydney IVF embryo culture medium suite (Cook Medical) or Gems sequential embryo culture media (Genea Biomedx).…”
Section: General Assisted Reproduction Proceduresmentioning
confidence: 99%
“…compared fertilization rates after physiological ICSI (PICS), IMSI and extraction of testicular sperm, respectively. They found that the use of testicular sperm significantly increased the fertilization rate, pregnancy rate and live birth rate after ICSI for patients with increased DNA fragmentation (Bradley et al ., ).…”
Section: Historical Overviewmentioning
confidence: 97%
“…They concluded that IMSI had no convincing improvement in clinical outcomes. They also reported that fertilization and blastocyst formation rates were not increased after IMSI than conventional ICSI (Bradley et al ., ).…”
Section: High Magnification Imaging Systemmentioning
confidence: 97%